2011
DOI: 10.1111/j.1745-4514.2011.00571.x
|View full text |Cite
|
Sign up to set email alerts
|

ANTIOXIDANT AND ANTIPROLIFERATIVE PROPERTIES OF HOT PEPPER (CAPSICUM ANNUUML.) SEEDS

Abstract: The antioxidant and antiproliferative activities of a methanol extract from hot pepper (Capsicum annuum L.) seeds (pepper seed extract [PSE]) were evaluated. The polyphenolic content of the PSE was 10.9 ± 0.0 mg gallic acid equivalents/g residue, and the capsaicin and dihydrocapsaicin contents were 22.7 and 6.5 mg/100 g of residue, respectively. The 2,2‐azino‐bis‐(3‐ethylbenzothiazoline‐6‐sulfonic acid) and 1,1‐diphenyl‐2‐picrylhydrazyl radical scavenging activities of hot pepper seeds were 38.6 ± 0.7 and 20.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…A study by Senawong et al [ 25 ] demonstrated the anti-proliferative activity of capsaicin without cell-cycle arrest property against HCT 116 cells. Furthermore, it was shown that pepper seed extract, at a concentration of 500 µg/ml, exhibited greater anti-proliferative activity (96.8%) and increased apoptotic cell population by 2.2-fold in HCT 116 cell line [ 26 ]. Like AITC discussed above, capsaicin was shown to restore wild type p53 activities by degrading mutant p53 protein in other human cancer lines U373 (glioblastoma) and SKBR3 (breast cancer) carrying p53 mutation, rendering cancer cells to be more susceptible to cancer drugs [ 27 ].…”
Section: Main Textmentioning
confidence: 99%
“…A study by Senawong et al [ 25 ] demonstrated the anti-proliferative activity of capsaicin without cell-cycle arrest property against HCT 116 cells. Furthermore, it was shown that pepper seed extract, at a concentration of 500 µg/ml, exhibited greater anti-proliferative activity (96.8%) and increased apoptotic cell population by 2.2-fold in HCT 116 cell line [ 26 ]. Like AITC discussed above, capsaicin was shown to restore wild type p53 activities by degrading mutant p53 protein in other human cancer lines U373 (glioblastoma) and SKBR3 (breast cancer) carrying p53 mutation, rendering cancer cells to be more susceptible to cancer drugs [ 27 ].…”
Section: Main Textmentioning
confidence: 99%
“…The authors found that the biologically active and total endotoxin concentration varied by location and that its concentration could be explained by meteorological data, wind speed, relative humidity, and dairy waste management practices. Jeon et al (2012) Lin, Huang, et al (2012) found that organic carbon, K + , and Clwere abundant in particles collected from the open burning of wax apple agricultural waste. The organic carbon/Na + , K + /Na + , and Cl -/Na + (mass) ratios in fine particles were 318, decreased.…”
Section: Chemical Characterizationmentioning
confidence: 99%
“…Hot pepper seed demonstrated significant health-promoting effects, having excellent anti-obesity activities (Jeon et al, 2010). In another study, hot pepper seeds showed strong antiproliferative activity against tumor cells (Jeon et al, 2012). As pepper seed is one of the major fruits in the world conferring health benefits due to their antioxidant activity (Kedage et al, 2007), phytosterols (Ruggieroa et al, 2013), and also contains a characteristic color value for seasonings, the present study aimed to evaluate the physicochemical changes in the seasonings by addition of various concentrations of pepper seed.…”
Section: Introductionmentioning
confidence: 99%